Addition of clonidine or fentanyl with bupivacaine for supraclavicular brachial plexus blocks in upper limb surgery - a randomized comparative study - Ahmed, Nasir Uddin; Hossain, Mozaffor; Akhtaruzzaman, AKM; Mondol, Montosh Kumar; Khatun, UH Shahera (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background The popularity of supraclavicular brachial plexus block in upper limb surgery in recent years are due to better understanding of using adjuvant to local anaesthetics, its advantages and in avoidance of the hazards of general anaesthesia. Objective To compare the quality of anaesthesia and duration of analgesia with clonidine-bupivacaine or fentanyl-bupivacaine in supraclavicular brachial plexus block. Method A total number of 60 patients (ASA class 1 and II) were selected randomly into two groups, thirty in each group. Group-A (control group) received fentanyl (100ìg) 2ml and bupivacaine (0.25%) 38ml, total of 40ml.Group-B (study group) received clonidine (150ìg) 2ml and bupivacaine (0.25%) 38ml, total of 40ml.The parameters including pulse rate, non-invasive systolic and diastolic blood pressure, respiratory rate, SpO2, onset and duration of motor and sensory block, post operative pain score in VAS, duration of analgesia, first analgesic demand, side effects were assessed and recorded. Result Onset and duration of sensory block were significantly higher in group-B than in group-A (P<0.001) and motor block were quite prolonged in group-B than group-A (p<0.001), prevalence of sedation in group-B slightly higher than group-A. But intensity of pain measured by VAS in group-A expressed highest at 8 hours of postoperative period and group-B shows highest VAS at 12 hours. Duration of effective analgesia (time from supraclavicular block to first analgesic demand) in study group-B had significantly longer mean duration than that produced by control group-A (14.4 ± 1.3 vs 10.9 ± 1.5 hours; P<0.001). Conclusion Clonidine and bupivacaine combination is a better alternative to fentanyl and bupivacaine in respect of quality of anaesthesia and duration of analgesia. DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19792 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 3-7